THE EFFECT OF GROWING MEDIUM MODIFICATION AND APPLICATION OF GROWTH REGULATORS ON THE GROWTH OF ORCHID PLANTS USING TISSUE CULTURE SYSTEM: LITERATURE REVIEW - Kukoh Puji Slamet Rahayu; Choirul Nisa Kismayanti, Septiana Kurniawati, Wima Rahayu Putri, Faridatul Zuhriyah, Alfina Damayant (Adisam Publisher, 2024)
Orchids are popular ornamental plants known for their beautiful flowers and limitless varieties. In addition to choosing the right growing medium, orchid care to support their growth also requires nutrients, one of which is growth regulators. Tissue culture is a propagation technique that can rapidly multiply orchid plants in large quantities. The research method involves a literature review by analyzing several relevant articles. The literature review discusses topics such as explant contamination, growing media, and growth regulators in orchid plants. Based on the research findings, the moth orchid (Phalaenopsis) can thrive and grow well in both VW (Vacin and Went) and MS (Murashige and Skoog) growing media. Meanwhile, the use of MS medium with the addition of the growth regulator BAP (Benzyl Adenine Purine) in black orchids has an impact on shoot multiplication.